Targeting Vesicular LGALS3BP by an Antibody-Drug Conjugate as Novel Therapeutic Strategy for Neuroblastoma - Capone, Emily (Cancers (Basel), 2020)
SIMPLE SUMMARY: Antibody Drug Conjugates are an emerging class of biopharmaceuticals that have seen an impressive increase of attention in the field of cancer therapy. Here, we describe the therapeutic activity of 1959-sss/DM3, a non-internalizing ADC targeting LGALS3BP, a secreted, extracellular vesicles-associated protein expressed by the majority of human cancers, including neuroblastoma. We show that 1959-sss/DM3 treatment can cure mice with established neuroblastoma tumours in pseudometastatic, orthotopic and Patient Derived Xenograft models. ABSTRACT: Neuroblastoma is the most common extra-cranial solid tumor in infants and children, which accounts for approximately 15% of all cancer-related deaths in the pediatric population. New therapeutic modalities are urgently needed. Antibody-Drug Conjugates (ADC)s-based therapy has been proposed as potential strategy to treat this pediatric malignancy. LGALS3BP is a highly glycosylated protein involved in tumor growth and progression. Studies have shown that LGALS3BP is enriched in extracellular vesicles (EV)s derived by most neuroblastoma cells, where it plays a critical role in preparing a favorable tumor microenvironment (TME) through direct cross talk between cancer and stroma cells. Here, we describe the development of a non-internalizing LGALS3BP ADC, named 1959-sss/DM3, which selectively targets LGALS3BP expressing neuroblastoma. 1959-sss/DM3 mediated potent therapeutic activity in different types of neuroblastoma models. Notably, we found that treatments were well tolerated at efficacious doses that were fully curative. These results offer preclinical proof-of-concept for an ADC targeting exosomal LGALS3BP approach for neuroblastomas.